Digest: Multiple selective pressures drive color diversity in moths. (12th January 2023) - Lungstrom, Linnea L; Fedder, Zachary
Abstract: How are color polymorphisms maintained within populations? De Pasqual et al. (2022) showed that female wood tiger moths ( Arctia plantaginis ) that were heterozygous for a wing color gene had higher fertility, hatching success, and offspring survival. These findings suggest that the complex interaction between heterozygote advantage and pleiotropic effects maintains color variability through a balance between multiple and competing selective pressures in wild populations.